2005
DOI: 10.4161/cc.4.4.1588
|View full text |Cite
|
Sign up to set email alerts
|

p14ARF Interacts with the SUMO-Conjugating Enzyme Ubc9 and Promotes the Sumoylation of Its Binding Partners

Abstract: Bcl-2 phosphorylation is a normal physiological process occurring at mitosis or during mitotic arrest induced by microtubule damaging agents. The consequences of Bcl-2 phosphorylation on its function are still controversial. To better understand the role of Bcl-2 phosphorylation in mitosis, we studied the subcellular localization of phosphorylated forms of Bcl-2. Immunofluorescence experiments performed in synchronized HeLa cells indicate for the first time that mitotic phosphorylated forms of Bcl-2 can be det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
52
1
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 91 publications
2
52
1
2
Order By: Relevance
“…Human p14 ARF has been reported to bind to several other proteins, including the WRN helicase, E2F1, c-Myc, topoisomerase I, HIF-1␣, the adenovirus E1A-regulated transcriptional repressor p120 E4F , and the HIV Tat-binding protein 1 (12,13,16,17,21,22,41). With the exception of c-Myc, which has not been tested, these proteins can undergo sumoylation when cotransfected with p14 ARF and His 6 -SUMO-1 into human tumor cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Human p14 ARF has been reported to bind to several other proteins, including the WRN helicase, E2F1, c-Myc, topoisomerase I, HIF-1␣, the adenovirus E1A-regulated transcriptional repressor p120 E4F , and the HIV Tat-binding protein 1 (12,13,16,17,21,22,41). With the exception of c-Myc, which has not been tested, these proteins can undergo sumoylation when cotransfected with p14 ARF and His 6 -SUMO-1 into human tumor cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…For example, might p19 Arf serve as a specificity factor that bridges Ubc9-containing complexes to Arf-binding proteins? Woods et al (21) stated that robust SUMO-1 conjugation of WRN could be observed in an in vitro reconstitution reaction in the presence of the SUMO E1͞E2 enzymes but indicated that addition of recombinant p14 ARF had no effect, even at limiting concentrations of Ubc9 with which tagged p14 ARF can coprecipitate when overexpressed (22). An inability to stimulate sumoylation in vitro with recombinant p14 ARF may not be surprising given the fact that Arf proteins are highly basic, bind nonspecifically to many acidic proteins and to nucleic acids, and normally reside in ''buffered'' higher-molecular-mass complexes in living cells (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26][27][28][29][30] Although ubiquitin was discovered more than 25 years ago, SUMO was discovered less than 10 years ago. However, this late entrant is becoming an important molecule in cell biology and cancer biology.…”
Section: Sumo Conjugation and Deconjugationmentioning
confidence: 99%
“…[24][25][26][27][28][29][30][31][32] The initial maturation step of SUMO requires C-terminal processing, leading to the exposure of a GG motif at its C-terminal end, allowing the conjugation process to occur. Following this step, heterodimeric E1 enzymes, SAE1/ SAE2, catalyze the ATP-dependent activation step.…”
Section: Sumo Conjugation and Deconjugationmentioning
confidence: 99%